2012
DOI: 10.1007/s10592-012-0330-5
|View full text |Cite
|
Sign up to set email alerts
|

Using molecular pedigree reconstruction to evaluate the long-term survival of outplanted hatchery-reared larval and juvenile northern abalone (Haliotis kamtschatkana)

Abstract: The restoration of abalone (Haliotis spp.) populations through supplementation with the offspring of hatchery-spawned wild parents has been attempted in several species, with variable results. Between 2002 and 2005, the Bamfield Huu-ay-aht Community Abalone Project released 4.5 million larvae and 152,000 juveniles of the northern abalone (Haliotis kamtschatkana) into Barkley Sound, BC. The purpose of this study was to estimate the long-term survival of outplanted abalone 3-7 years after their release and thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…For example, long‐term survival of out‐planted abalone ( Haliotis kamtschatkana ; Read et al . ) and reproductive success in Pacific salmon ( Oncorhynchus spp. ; Baumsteiger et al .…”
Section: Meta‐analysis Of the Use Of Genetics In Ecological Restorationmentioning
confidence: 99%
“…For example, long‐term survival of out‐planted abalone ( Haliotis kamtschatkana ; Read et al . ) and reproductive success in Pacific salmon ( Oncorhynchus spp. ; Baumsteiger et al .…”
Section: Meta‐analysis Of the Use Of Genetics In Ecological Restorationmentioning
confidence: 99%
“…Schiel & Welden 1987, Tegner & Butler 1985, Tegner 2000, James et al 2007, Roberts et al 2007, Hamasaki & Kitada 2008. Long-term survival of hatchery released larvae and juveniles was recently assessed by Read et al (2012), who found that up to 26% of emergent adults were from hatcheries. While this is encouraging, the overall density was still considered to be low.…”
Section: Implications For Restorationmentioning
confidence: 99%
“…This suggests restoration efforts are needed if abalone populations are to recover. One potential solution, the outplanting of hatchery-reared H. kamtschatkana, has so far been limited by high mortality rates of hatchery abalone when released into the wild (Read, Lemay, Acheson & Boulding 2012;Hansen & Gosselin 2013;Read, Lessard & Boulding 2013). For H. kamtschatkana, the mortality rate of recently outplanted juveniles has been estimated at 66% over 2 weeks (Hansen & Gosselin 2013), while the mortality rate of wild individuals of the same age in the same region is <1% over the same duration (Breen 1980(Breen , 1986Fournier & Breen 1983;Sloan & Breen 1988).…”
Section: Introductionmentioning
confidence: 99%